2020
DOI: 10.1109/access.2020.3031155
|View full text |Cite
|
Sign up to set email alerts
|

Piano Automatic Computer Composition by Deep Learning and Blockchain Technology

Abstract: To explore the automatic computer composition, investigate the copyright protection and management of digital music, and expand the application of deep learning and blockchain technologies in the generation of digital music works, piano composition was taken as a sample. First, through the elaboration of the neural network methods based on deep learning, the Recurrent Neural Network (RNN), Long-Short-Term Memory (LSTM), and Gated Recurrent Unit (GRU) networks were introduced, and the deep learning-based GRU-RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In contrast, the total time taken by the eight experiments is basically about 4–5 seconds, and the time-consuming of the work uplink and confirmation process is controlled at about 4 seconds. In addition, Li [ 33 ] conducted research on automatic piano composition and recognition technology based on DL and introduced the RNN, LSTM, and Gated Recurrent Unit (GRU) network and DL-based neural networks. The findings indicate that the GRU-RNN model shows satisfactory results in both manual analysis evaluation or paragraph pause analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the total time taken by the eight experiments is basically about 4–5 seconds, and the time-consuming of the work uplink and confirmation process is controlled at about 4 seconds. In addition, Li [ 33 ] conducted research on automatic piano composition and recognition technology based on DL and introduced the RNN, LSTM, and Gated Recurrent Unit (GRU) network and DL-based neural networks. The findings indicate that the GRU-RNN model shows satisfactory results in both manual analysis evaluation or paragraph pause analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Through experiments, the authors proved that this audiocombined video data transcription method could improve the quality of music transcribed from each mode alone. Li (2020) took piano composition as a sample to explore computer automatic composition and analyzed the application of DL and blockchain to the generation of digital music works. They reported that DL had great application potential in computer automatic composition of digital music, and the integration of blockchain and DL had played a role in promoting the expansion and popularization of the digital music market.…”
Section: Related Workmentioning
confidence: 99%
“…In [8], first, through the elaboration of the neural network techniques dependent on deep learning, the recurrent neural network (RNN), long short-term memory (LSTM), and gated recurrent unit (GRU) networks were presented, and the deep learning-based GRU-RNN programmed piece model was built. Second, the blockchain innovation was broken down and communicated, and the issues in the conventional copyright security and the board of computerized music were dissected.…”
Section: Related Workmentioning
confidence: 99%